ENHANCING FOOD CROP PRODUCTION THROUGH ROTATORY CREDIT SAVINGS AMONG SMALL HOLDER FOOD CROP FARMERS IN DEMSA LOCAL GOVERNMENT AREA OF ADAMAWA STATE, NIGERIA - Sunday Francis YUSTUS; Sani Gaya SAIDU; Dengle Yuniyus GIROH (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Enhancing Food Crop Production through Rotatory Credit Savings among Small holder Food Crop Farmers in Demsa Local Government Area of Adamawa State, Nigeria was the focus of this research. A random sample of 120 respondents were collected and data subjected to descriptive and inferential statistics. Findings revealed that 81.67% of the respondents fall within the age range of 25 to 49 years with mean age of 35 years, males dominated the association (66.67%), 70.83 % were married with mean annual saving of N31, 345.50. Regression analysis revealed that about 71.21 % of the differences in the savings of respondents were explained by the variables included in the model (R2=0.7121). Age, education, income and farm size were the determinants of savings among respondents.